2021
DOI: 10.3390/ijms23010365
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Neutrophils in the Pathogenesis of Chronic Lymphocytic Leukemia

Abstract: Tumor-associated neutrophils appear to be a crucial element of the tumor microenvironment that actively participates in the development and progression of cancerous diseases. The increased lifespan, plasticity in changing of phenotype, and functions of neutrophils influence the course of the disease and may significantly affect survival. In patients with chronic lymphocytic leukemia (CLL), disturbances in neutrophils functions impede the effective immune defense against pathogens. Therefore, understanding the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 82 publications
0
8
0
2
Order By: Relevance
“…In addition, neutrophils infiltrated in the leukemic niche were observed to secrete survival cytokines, including APRIL and BAFF, which are important for B cell proliferation. Finally, the neutrophil depletion in Eμ-TCL1 mice, with already developed CLL, demonstrated a reduction in the leukemic burden in spleens, clearly showing that neutrophils support leukemia progression in Eμ-TCL1 mice ( 65 , 66 ).…”
Section: Tumor-associated Neutrophils (Tans)mentioning
confidence: 84%
See 1 more Smart Citation
“…In addition, neutrophils infiltrated in the leukemic niche were observed to secrete survival cytokines, including APRIL and BAFF, which are important for B cell proliferation. Finally, the neutrophil depletion in Eμ-TCL1 mice, with already developed CLL, demonstrated a reduction in the leukemic burden in spleens, clearly showing that neutrophils support leukemia progression in Eμ-TCL1 mice ( 65 , 66 ).…”
Section: Tumor-associated Neutrophils (Tans)mentioning
confidence: 84%
“…Indeed, stromal cells from the leukemic microenvironment have been shown to interact substantially with neutrophils ( 65 , 66 ). A study realized in an Eμ-TCL1 CLL murine model indicated that stromal cells from red pulp and the marginal zone of spleens presented LCs infiltrate, overexpressed genes related to neutrophil chemotaxis, including the chemotactic factors S100A8 and S100A9 (MRP8 and MRP14, respectively), the chemokine receptor CXCR2, the pro-inflammatory cytokine IL-1β, and integrin CD11b (Itgam) ( 65 , 66 ). In addition, neutrophils infiltrated in the leukemic niche were observed to secrete survival cytokines, including APRIL and BAFF, which are important for B cell proliferation.…”
Section: Tumor-associated Neutrophils (Tans)mentioning
confidence: 99%
“…Although our data confirm that phagocytes including resident monocytes support T-ALL progression, targeting these cells did not improve mice survival. We also independently studied neutrophils, a key cell population in inflammation, and showed that these cells are not implicated in T-ALL progression, albeit participating in other hematological malignancies like Chronic Lymphocytic Leukemia 54 or B lymphomas 55 . Studying the role of neutrophils and resident monocytes in T-ALL was also motivated by their crucial and complex role in infections 56 or in cancers 57 and since they are the most increased cell populations in the periphery of our leukemic mice.…”
Section: Discussionmentioning
confidence: 99%
“…Нейтрофилы реагируют на различные медиаторы, высвобождаемые в микроокружении опухоли, что приводит к активации их либо противоопухолевых, либо проопухолевых фенотипов. Данная нейтрофильная пластичность обусловлена влиянием трансформирующего фактора роста β (TGFß), β-интерфероном (ИФН-β), ИЛ-35, а также концентрацией цитокинов и кислорода в микроокружении опухоли [4].…”
Section: роль нейтрофилов в развитии ракаunclassified
“…Противоопухолевая активность нейтрофилов N1 связана с прямым уничтожением опухолевых клеток путем выработки активных форм кислорода (АФК) и оксида азота или индукцией апоптоза, связанного с активацией Fas/TRAIL. Другие механизмы включают антителозависимую клеточно-опосредованную цитотоксичность (ADCC) и активацию функции Т-клеток [8].…”
Section: роль нейтрофилов в развитии ракаunclassified